World Workshop on Oral Medicine VII: Prognostic biomarkers in oral leukoplakia: A systematic review of longitudinal studies. (29th May 2019) - Villa, Alessandro; Celentano, Antonio; Glurich, Ingrid; Borgnakke, Wenche S.; Jensen, Siri Beier; Peterson, Douglas E.; Delli, Konstantina; Ojeda, David; Vissink, Arjan; Farah, Camile S.
Abstract: Objective: To identify the prognostic biomarker candidates for stratification and long‐term surveillance of oral leukoplakia progressing to cancer via a systematic literature review. Materials and Methods: Systematic searches with no date restrictions were conducted on March 29, 2018, targeting the databases PubMed (Ovid), EMBASE (Ovid), EBM (Ovid), and Web of Science (ISI). Bias was assessed using the Quality in Prognosis Studies tool. Biomarkers were stratified based on hallmarks of cancer. Results: Inclusion criteria were met by 25 of 3, 415 studies. A range of biomarkers were evaluated experimentally for risk stratification, prognosis, and surveillance of oral leukoplakia in tissue, blood, and saliva. However, the studies were highly heterogeneous and require further validation. Biomarkers reported in these studies included inflammatory or oxidative markers, growth factors, ion channels, genetic and cellular regulatory factors, and epigenetic biomarkers. Studies tended to include small sample sizes, under‐reported or variably reported histopathological data, did not address potential confounding, reported limited/variable follow‐up data, or lacked a control group. Inclusion of subsets from chemoprevention trials may have introduced bias regarding reported malignant transformation rates and accuracy of prognostic biomarkers. Conclusions: This review identified insufficient longitudinal evidence to support validated prognostic biomarkers for oral leukoplakia. Further studies are needed to identify molecular targets with the potential to mitigate risk of malignant transformation.